Efficacy and mechanisms of lumbopelvic manipulation combined with Baduanjin exercise for postpartum low back pain: a study protocol for a randomized controlled trial - Guofang Huang; Yuxian Xiong; Xikui Zhang; Yanjun Hou; Jiamin Chen (Frontiers in Medicine, 2026)
Introduction Postpartum low back pain (PLBP) is common among puerperal women, with complex etiology involving spinal-pelvic changes and reduced core stability. It often becomes chronic, impairing quality of life and mental health. Non-pharmacological therapies are widely used and show good outcomes, but high-quality RCTs are limited, and objective evidence of core muscle activation after combined manual therapy and Baduanjin is lacking. Baduanjin is a traditional Chinese mind-body exercise that uses gentle movements and coordinated breathing to enhance core stability, making it particularly suitable for postpartum women. Previous studies have demonstrated its effectiveness in reducing pain and improving function in patients with chronic low back pain, with preliminary evidence also supporting its benefits in the postpartum population. This gap undermines the protocol's credibility and clinical uptake. Therefore, this study aims to evaluate the efficacy of lumbopelvic manipulation plus Baduanjin for PLBP, and to explore neuromuscular mechanisms using surface electromyography (sEMG). Methods and analysis This single-center, assessor-blinded RCT will enroll 50 participants randomized 1:1 to control (health education + lumbopelvic manipulation) or experimental group (same plus Baduanjin). The control group will receive lumbopelvic manipulation (15 min/session, three times per week), while the experimental group will receive the same manipulation plus supervised Baduanjin exercise (12 min/session, three times per week) for 4 weeks. The 4-week intervention is followed by follow-up assessments at weeks 8 and 12. Primary outcome: pain intensity (Numerical Pain Rating Scale, NPRS). Secondary outcomes: functional disability (Oswestry Disability Index, ODI), quality of life (SF-36), and sEMG parameters (%MVIC and mean power frequency, MPF) of the lumbar extensors (erector spinae and multifidus) and abdominal wall muscles (rectus abdominis, external/internal oblique, and transversus abdominis). Assessments at baseline (week 0) and week 4; NPRS, ODI, SF-36 also at weeks 8 and 12. Discussion This trial will evaluate the efficacy of lumbopelvic manipulation combined with Baduanjin exercise for postpartum low back pain, a population with limited medication options during lactation. The inclusion of sEMG alongside patient-reported outcomes will provide objective evidence on neuromuscular changes, extending current evidence that has relied primarily on subjective measures. Clinical Trial Registration: https://itmctr.ccebtcm.org.cn , identifier: ITMCTR2025001056.